Perceived Barriers and Facilitators of Implementing a Multicomponent Intervention to Improve Communication With Older Adults With and Without Dementia (SHARING Choices) in Primary Care: A Qualitative Study. (November 2022) - Smith, Kelly M.; Scerpella, Danny; Guo, Amy; Hussain, Naaz; Colburn, Jessica L.; Cotter, Valerie T.; Aufill, Jennifer; Dy, Sydney M.; Wolff, Jennifer L.
Introduction: Implementing patient- and family-centered communication strategies has proven challenging in primary care, particularly for persons with dementia. To address this, we designed SHARING Choices, a multicomponent intervention combining patient and family partnered agenda setting, electronic portal access, and supports for advance care planning (ACP). This qualitative descriptive study describes factors affecting SHARING Choices implementation within primary care. Methods: Semi-structured interviews or focus groups with patient/family dyads (family, friends, unpaid caregivers) and primary care stakeholders (clinicians, staff, administrators) elicited perceived barriers and facilitators of SHARING Choices implementation. Field notes and interview transcripts were coded using template analysis along the Consolidated Framework for Implementation Research (CFIR) constructs. Content analysis identified themes not readily categorized within CFIR. Results: About 22 dyads, including 14 with cognitive impairment, and 30 stakeholders participated in the study. Participants were receptive to the SHARING Choices components. Enablers of SHARING Choices included adaptability of the intervention, purposive engagement of family (particularly for patients with dementia), consistency with organizational priorities, and the relative advantage of SHARING Choices compared to current practices. Perceived barriers to implementation included intervention complexity, space constraints, workflow, and ACP hesitancy. The ACP facilitator was perceived as supportive in addressing individual and organizational implementation barriers including patient health and technology literacy and clinician time for ACP discussions. Conclusions: Patients, family, and primary care clinicians endorsed the objectives and individual components of SHARING Choices. Strategies to enhance adoption were to simplify materials, streamline processes, leverage existing workflows, and embed ACP facilitators within the primary care team.